Water quality control on fish aquarium using Fuzzy Logic method - Alfanz, Rocky; Wiryadinata, Romi; Sobar, Fragrans Anjasmara; Muttakin, Imamul; Setiawan, Ipick; Maulana, Alief (Journal Industrial Servicess, 2023)
Indonesia, as an archipelagic country, boasts abundant fishery resources. The effective development of these resources has the potential to yield sustainable benefits, contributing to the prosperity of its people. Maintaining water quality plays a pivotal role in advancing fish farming practices, hence the necessity for water quality analysis. This study endeavors to design and construct a control system tailored for freshwater fish aquariums, employing Fuzzy logic methods. This system incorporates pH, temperature, and total dissolved solid sensors, aiming to regulate the duration of the water pump and heater operation based on Fuzzy-derived decisions when the setpoint values for pH, temperature, and TDS are not met. Analysis of water quality measurements demonstrates the tool's capability to achieve a pH measurement accuracy of 99.17%, temperature accuracy of 99.10%, and TDS accuracy of 99.44%.